Letter : Homes for Spanish orphans - Ford, Sidney G.
030-0109-001 TELEPHONE: MUSEUM 8886 TELEGRAMS: Minfedbrit, Westcent, London THE MINEWORKERS' FEDERATION OF GREAT BRITAIN 50, Russell Square, London W.C.1 22nd July, 1938. Secretary: EBBY EDWARDS Sir Walter M. Citrine, T.U.C., Transport House, Smith Square, S.W.1. Dear Sir Walter, Homes for Spanish Orphans. In the absence of Mr. Edwards, I have to acknowledge receipt of your letter of the 21st inst. Mr. Schevenels' report has been sent to Mr. Edwards at Whitley Bay and no doubt he will mention the matter to you some time next week. Yours sincerely, Sidney G. Ford 292/946/30/109